Clinical Applications of Whole-slide Imaging in Anatomic Pathology. (July 2017) - Volynskaya, Zoya; Evans, Andrew J.; Asa, Sylvia L.
Abstract : The development of whole-slide imaging has paved the way for digitizing of glass slides that are the basis for surgical pathology. This transformative technology has changed the landscape in research applications and education but despite its tremendous potential, its adoption for clinical use has been slow. We review the various niche applications that initiated awareness of this technology, provide examples of clinical use cases, and discuss the requirements and challenges for full adoption in clinical diagnosis. The opportunities for applications of image analysis tools in a workflow will be changed by integration of whole-slide imaging into routine diagnosis.